2020
DOI: 10.21203/rs.3.rs-21868/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of deranged thyroid function parameters in children admitted for management of diabetic ketoacidosis/diabetic ketosis

Abstract: Background: Euthyroid sick syndrome (ESS) frequently arises in children admitted with diabetic ketoacidosis/diabetic ketosis (DKA/DK). This study evaluates the interplay of various metabolic factors with occurrence of deranged thyroid function tests in children suffering from DKA/DK.Methods: 98 DKA and 96 DK pediatric patients were selected from hospital records. Those on thyroxine replacement, with overt hypothyroidism, or with positive anti-thyroperoxidase (TPO) antibody were excluded. Tests for liver functi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Serum albumin levels were shown to be reduced in ESS pediatric patients with DK/DKA [24]. Besides the aforementioned in uencing factors, the de ciency of insulin can also cause a drop in albumin in DK/DKA, since albumin synthesis in hepatocytes depends on su cient insulin secretion [9,45]. In the present research, albumin de ciency was also indicated to be an independent risk factor for ESS, and its reduction might present a worse prognosis in DK/DKA patients.…”
Section: Analysis Of Correlated Factors Of Thyroid Hormonessupporting
confidence: 54%
See 2 more Smart Citations
“…Serum albumin levels were shown to be reduced in ESS pediatric patients with DK/DKA [24]. Besides the aforementioned in uencing factors, the de ciency of insulin can also cause a drop in albumin in DK/DKA, since albumin synthesis in hepatocytes depends on su cient insulin secretion [9,45]. In the present research, albumin de ciency was also indicated to be an independent risk factor for ESS, and its reduction might present a worse prognosis in DK/DKA patients.…”
Section: Analysis Of Correlated Factors Of Thyroid Hormonessupporting
confidence: 54%
“…The reduction of FT3 is an adaptive response to stress during the acute phase response in critical illness [21][22] and the serum level of FT3 could return to normal with treatment and recovery of illness [23]. Shao et al found that the ESS patients with DKA in children had lower serum FT3, FT4 and TSH, accompanied with worse glucose control [9]. Previous studies demonstrated high prevalence of thyroid dysfunction in DKA patients [19,24].…”
Section: Analysis Of Correlated Factors Of Thyroid Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, it was noted that there may be an interplay of factors for diabetes mellitus and thyroid disorder that put these children more at risk. A higher degree of acidosis was associated with children who had lower levels of free thyroid hormones and euthyroid sick syndrome [ 36 ]. In one pediatric study, the prevalence of hypothyroidism was higher in children and adolescents with T1DM [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic diuresis depletes fluid and electrolytes and increases free fatty acids, consequently eliciting severe dehydration and acidemia, sometimes resulting in fatal conditions. In DKA pathophysiology, the consequence of metabolic decompensation has been negatively associated with various endocrine functions, including thyroid [ 6 , 7 ] and growth hormone [ 8 ] functions. Although Hu et al [ 9 ] recently reported that patients with DKA and euthyroid sick syndrome were shown to have poor glycemic control during the initial days of treatment, the long-term prognosis related to endocrinologic derangement in DKA patients has not yet been well documented.…”
Section: Introductionmentioning
confidence: 99%